Systematic literature review of marine lives: the “thwack” of inexperience divers towards coral reefs / Quratul Ain Syahirah Awang Ali, Tressy Belly and Muhammad Zulhilmi Zulkurnain - Awang Ali, Quratul Ain Syahirah; Belly, Tressy; Zulkurnain, Muhammad Zulhilmi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Diving tourism, commonly referred to as scuba diving tourism, has emerged as a recreational activity that enables people to explore underwater surroundings and more carefully see the grandeur of aquatic life. Nevertheless, while diving tourism has played a substantial part in expanding people's awareness of the importance of marine environmental preservation, there are unethical dive practises, such as harming or destroying coral reefs, taking marine creatures as souvenirs, and improper trash disposal, that may have a detrimental effect on the marine ecosystem. Therefore, this study aims to investigate the factors causing coral reef destruction as a result of activities, particularly among inexperienced divers that involves in Discover Scuba Diving (DSD). Systematic Literature Review (SLR) method and The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach were used to analyse the previous studies based on the keyword search. Findings shows that, poor planning, lack of education/knowledge/information, inexperience divers are being ignorant, irresponsible behaviour, impact of diving equipment (e.g., fins, tanks), camera used, buoyancy control, incorrect weight and cognitive (e.g., stress, anxiety) are among the factors the deteriorate the environment of coral reefs. Implications are also discussed in this study.